The Effect of Training and Application of Disciplinary Sanctions on Work Discipline of Civil Service Police Unit - Akhmad Aspiannor (PT. Hanken Sukses Jaya, 2022)
As an institution tasked with maintaining order and enforcing regional regulations, work discipline is an absolute for officers in the Civil Service Police Unit. This work discipline is related to training and application of sanctions obtained by officers so that they can realize optimal discipline. The purpose of this study was to analyze the effect of training variable and application of disciplinary sanctions variable on work discipline in Civil Service Police Unit of Saouth Kalimantan Province. This study uses descriptive quantitative methods through questionnaires with a sample of 92 respondents who have served more than 1 year. From the result of mutiple regression analysis with SPSS, the calculated F value is 39.707 which means that training and application of disciplinary sanctions simultaneously affect work discipline. The result of t-test analysis stated that training was 5.320 and application of disciplinary sanctions was 4.081 which means that it has a significant effect on work discipline